Comparing the risks of hospitalized heart failure associated with glinide, sulfonylurea, and acarbose use in type 2 diabetes: A nationwide study. (1st February 2017) - Lee, Yen-Chieh; Chang, Chia-Hsuin; Dong, Yaa-Hui; Lin, Jou-Wei; Wu, Li-Chiu; Hwang, Jing-Shiang; Chuang, Lee-Ming
Abstract: Background: Increasing evidence suggests that certain newer anti-diabetic drugs are associated with an increased risk of hospitalized heart failure (HHF). However, the potential risks associated with the use of sulfonylurea and glinide have not been carefully evaluated. Methods: A retrospective cohort study using the Taiwan National Health Insurance claims database was conducted to examine the risks of HHF among newly diagnosed type 2 diabetic patients who initiated glinide, sulfonylurea, or acarbose therapy during 2006–2012. The outcome of interest was hospitalization due to heart failure after treatment initiation, defined by ICD-9-CM code. A Cox proportional hazard regression model was used to calculate the hazard ratio (HR) and 95% confidence interval (CI) using acarbose as the reference group. Results: A total of 25, 638 glinide, 272, 140 sulfonylurea, and 29, 376 acarbose initiators were included in the analysis. Patients who initiated glinide had the highest crude HHF incidence. In the analysis adjusted for baseline differences, a significantly higher risk of HHF was found for glinide (adjusted HR, 1.53; 95% CI, 1.24–1.88), but not for sulfonylurea (adjusted HR, 0.94; 95% CI, 0.80–1.11), as compared with acarbose. The elevated risk remained consistent across different subgroups of patients as well as several sensitivity analyses including exploring the impact of potential unmeasured confounding. Conclusions: These findings indicated that, as compared with acarbose, glinide may be associated with a higher risk of HHF for type 2 diabetic patients. Further researchis needed to fully evaluate the risks and benefits of glinide therapy relative to other oral anti-diabetic agents.